The Influence of User Interface (UI) and User Experience (UX) on Purchase Decisions and User Satisfaction on E-Commerce Platforms - Muhammad Fathi Farhan; Dr. Osly Usman, M.Bus Syst (Journal of Strategic Marketing and Innovation, 2025)
Currently, technology plays a significant part in the lives of humans, in addition to the development of the internet, one of which influences people's lifestyles, especially in shopping for basic necessities online through e-commerce platforms because of their easy transaction process. The purpose of this research is to examine the impact of user interface design and user experience on purchase decisions and user satisfaction on e-commerce platforms. With the use of SmartPLS 4.0 software, this study employs a quantitative methodology utilizing the Partial Least Square (PLS) method. An alternate technique to structural equation modeling (SEM) is PLS. A questionnaire was used to obtain the data with a sample of 100 respondents from the Faculty of Economics and Business, Jakarta State University. The study's findings indicate that while user interface design significantly influences both customer satisfaction and purchase decisions, user experience has no discernible impact on either of these variables It is anticipated that this study will serve as a helpful, current resource for digital media platforms, practitioners, organizations, and businesses in preserving user satisfaction in the quickly evolving digitalization era.